Perinatal Outcome of Previable Premature Rupture of Membranes Before 24 Weeks of Gestation: A Single-Centered Retrospective Cohort Study - Yasemin Dogan; Ercan Kockaya; Muzeyyen Dilsad Eser; Ayla Gunlemez (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Preterm premature rupture of membranes (PPROM) has unfavorable consequences for the neonate and the mother if it occurs before 24 weeks of gestation. We aim to present our series to elucidate the course of previable PPROM and to detect maternal and neonatal outcomes.